2006
DOI: 10.1007/s00405-006-0165-0
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic laryngeal spasm: management and long-term outcome

Abstract: Idiopathic laryngeal spasm (ILS) is an uncommon disorder characterised by brief episodes of stridor, occurring at any time. Subsequent outpatient ENT examination is normal. These episodes cause considerable anxiety for both patient and physician. Little is known about the initiating event(s) in this condition or the long-term outcome. Using a combination of telephone and postal questionnaires with case note review, we have reviewed a cohort of 21 patients with this diagnosis managed by the senior author over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The causes of laryngospasm may include endotracheal maneuvers, reflux esophagitis, amyotrophic lateral sclerosis, and hypomagnesemia [9][10][11] . Idiopathic cases of recurrent laryngospasm with no apparent cause have also been reported 12,13) . Darren reported that most patients diagnosed with idiopathic laryngospasm have attacks at any time that last less than 2 min 13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of laryngospasm may include endotracheal maneuvers, reflux esophagitis, amyotrophic lateral sclerosis, and hypomagnesemia [9][10][11] . Idiopathic cases of recurrent laryngospasm with no apparent cause have also been reported 12,13) . Darren reported that most patients diagnosed with idiopathic laryngospasm have attacks at any time that last less than 2 min 13) .…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic cases of recurrent laryngospasm with no apparent cause have also been reported 12,13) . Darren reported that most patients diagnosed with idiopathic laryngospasm have attacks at any time that last less than 2 min 13) . Laryngospasm is relieved in a short time by a decrease in the partial pressure of oxygen in the blood, an increase in the partial pressure of carbon dioxide, and resumption of inspiration 14) .…”
Section: Discussionmentioning
confidence: 99%
“…6 Paroxysmal laryngospasm, dyspnea with exertion, or stridor are a frightening and debilitating clinical problems that have a major impact on quality of life. 4 Paroxysmal laryngospasm is usually a benign and selflimiting condition with various causative factors, including laryngopharyngeal reflux, allergy, upper respiratory tract infection, and psychiatric disorders. 3,4,19 Patients with paroxysmal laryngospasm due to the above factors were excluded from the present study.…”
Section: Discussionmentioning
confidence: 99%
“…4 Paroxysmal laryngospasm is usually a benign and selflimiting condition with various causative factors, including laryngopharyngeal reflux, allergy, upper respiratory tract infection, and psychiatric disorders. 3,4,19 Patients with paroxysmal laryngospasm due to the above factors were excluded from the present study. Laryngospasm occurred after UVCP in all cases in this series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation